Ipad Text-to-Speech and Repeated Reading to Improve Reading Comprehension for Students with SLD - Alqahtani, Saeed S. (Reading & writing quarterly, 2023)
Students with specific learning disabilities (SLD) have difficulty with most reading skills, including reading comprehension. Improving reading comprehension skills requires efficient interventions that consider both meaning- and code-based skills simultaneously. Using a single-subject multiple-baseline design across participants, with alternating treatment design, this study compared two reading interventions (repeated reading vs. iPad text-to-speech) combined with a meta-cognitive strategy (question generation). Three fourth-grade and third-grade students who had been diagnosed by their school as having reading difficulties participated in the study. Using the index of narrative complexity, two participants showed improvement in reading comprehension skills. However, there were slight differences for the RAAC intervention over the iPad intervention for one participant. The time required to administer the iPad intervention was shorter than the time required to administer the Reread-Adapt and Answer-Comprehend (RAAC) intervention (an average of 12.73 min for the repeated reading vs. 5.45 min for the iPad).